Islamic Education as an Agent of Social Change: A Sociological Study of the Goals of Community-Based Education - Zakiyah Nur Azizah; Wihdatul Rohani (Lembaga Yasin AlSys, 2026)
Amid globalization, Islamic education is often confined to ritual and cognitive domains, thereby overlooking its transformative potential as a catalyst for social change. This study aims to examine the role of Islamic education in promoting social transformation through a sociological analysis of community-based educational objectives. Employing a qualitative literature-based methodology, relevant sources were selected purposively and analyzed using content analysis. The findings indicate that community-oriented Islamic education seeks to balance individual piety (habluminallah) and collective welfare (habluminannas) as the foundation for cultivating a civilized society. Islamic education functions as a medium of value transformation by responding to moral crises, individualism, and community disempowerment. However, a gap remains between its ideal objectives and practical implementation. To address this gap, three strategic directions are emphasized: updating curricula to engage with real-world social issues, strengthening humane social character, and fostering close collaboration among schools, families, and communities. This study concludes that Islamic education can serve as a responsive and adaptive force for social reconstruction in the modern era. Its contribution lies in reaffirming the sociological relevance of community-based Islamic education for advancing justice, social equity, and a more dignified collective future.